PENGGUNAAN METODE MONTESSORI DALAM KEGIATAN MENULIS DI PAUD - Nadar, Wahyuni; Kusumawati Wijaya, Purwani (LPPM Sekolah Tinggi Ilmu Tarbiyah Al Marhalah Al Ulya Bekasi, Indonesia, 2022)
This research was conducted based on the findings of problems related to children's writing skills in PAUD. These problems require the need for an approach, method or learning model to handle it. The learning developed is learning through the Montessori method. Writing for early childhood is a classic problem that is of special note to parents and teachers. In writing, children are not only required to have maturity in the language aspect, but must be ready in the aspects of fine motor and cognitive development. The Montessori Method is one of the writing methods that can be applied in PAUD because this method can be integrated into all aspects, has media that Interesting and easy steps. The purpose of this study was to obtain an overview of the use of the Montessori method in improving early childhood writing skills in PAUD. This study uses a qualitative method. Data collection techniques in this study are through observation, interviews, and documentation.